Erythroxylum pungens Tropane Alkaloids: GC-MS Analysis and the Bioactive Potential of 3-(2-methylbutyryloxy)tropan-6,7-diol in Zebrafish (Danio rerio) - Gondim Lambert Moreira, Letícia; Leite Ferreira, Maria Elisa; Reginaldo, Fernanda Priscila Santos; Lourenço, Estela Mariana Guimarães; Zuanazzi, José Angelo Silveira; Barbosa, Euzébio Guimarães; Ferreira, Leandro de Santis; Fett-Neto, Arthur Germano; Cavalheiro, Alberto José; Luchiari, Ana Carolina; Giordani, Raquel Brandt (Planta Medica, 2020)
Tropane alkaloids are specialized plant metabolites mostly found in the Erythroxylaceae and Solanaceae families. Although tropane alkaloids have a high degree of structural similarity because of the tropane ring, their pharmacological actions are quite distinct. Brazil is one of the main hotspots of Erythroxylum spp. diversity with 123 species (almost 66% of the species catalogued in tropical America). Erythroxylum pungens occurs in the Caatinga, a promising biome that provides bioactive compounds, including tropane alkaloids. As part of our efforts to investigate this species, 15 alkaloids in specimens harvested under different environmental conditions are presented herein. The occurrence of 3-(2-methylbutyryloxy)tropan-6,7-diol in the stem bark of plants growing in their natural habitat, greenhouse controlled conditions, and after a period of water restriction, suggests that it is a potential chemical marker for the species. This alkaloid was evaluated for several parameters in zebrafish (Danio rerio) as a model organism. Regarding toxicity, teratogenic effects were observed at 19.5 µM and the lethal dose for embryos was 18.4 µM. No mortality was observed in adults, but a behavioral screen showed psychostimulatory action at 116.7 µM. Overall, the alkaloid was able to cause zebrafish behavioral changes, prompting further investigation of its potential as a new molecule in the treatment of depression-like symptoms. In silico, targets involved in antidepressant pathways were identified by docking.
Keywords: Erythroxylum pungens; Erythroxylaceae; tropane alkaloids; Danio rerio; Cyprinidae; Caatinga